2007
DOI: 10.3174/ajnr.a0645
|View full text |Cite
|
Sign up to set email alerts
|

Improved Identification of Intracortical Lesions in Multiple Sclerosis with Phase-Sensitive Inversion Recovery in Combination with Fast Double Inversion Recovery MR Imaging

Abstract: BACKGROUND AND PURPOSE:Accurate detection and classification of purely intracortical lesions in multiple sclerosis (MS) are important in understanding their role in disease progression and impact on the clinical manifestations of the disease. However, detection of these lesions with conventional MR imaging remains a challenge. Although double inversion recovery (DIR) has been shown to improve the sensitivity of the detection of cortical lesions, this sequence has low signal-to-noise ratio (SNR), poor delineati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
180
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(187 citation statements)
references
References 23 publications
7
180
0
Order By: Relevance
“…The detected cortical lesion load is comparable with the bulk of cortical lesions assessed by specialized MR imaging methods developed for sensitive cortical lesion delineation. 13,15,16,18,29 While it has been reported that cortical lesions are more conspicuous on 3D double inversion recovery compared with 3D-FLAIR images, 13,17 the former is not yet widely available on clinical scanners. FLAIR hyperintensities might represent lesions, perivenular spaces, or CSFrelated flow artifacts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The detected cortical lesion load is comparable with the bulk of cortical lesions assessed by specialized MR imaging methods developed for sensitive cortical lesion delineation. 13,15,16,18,29 While it has been reported that cortical lesions are more conspicuous on 3D double inversion recovery compared with 3D-FLAIR images, 13,17 the former is not yet widely available on clinical scanners. FLAIR hyperintensities might represent lesions, perivenular spaces, or CSFrelated flow artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…We detected cortical lesions in 92.3% of patients, supporting the notion that focal cortical lesions are highly prevalent in MS. 6,11,[13][14][15][16]30 Cortical lesions occurred in all studied clinical subgroups, including 85.7% of patients with Early RR MS. These results are consistent with recent MR imaging studies that detected cortical lesions from the earliest clinical stages of MS, even in patients with clinically isolated syn- drome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Double inversion recovery (DIR) MR imaging is useful for the detection of cortical lesions. [22][23][24] This technique is based on a 3D…”
mentioning
confidence: 99%